Pengelolaan Sampah Di Era Revolusi Industri 4.0 Berbasis Startup Digital - Septiana Dewi Andriana; Dzikriy Al-Muntazhim Lubis; Ashri Prastiko Juned; Hasdiana Hasdiana (Query: Journal of Information Systems, 2019)
Waste is one of the problems that often arise in every major city. Poor waste management is the main cause of the problem. If it is not dumped in a certain area, waste management generally only reaches the combustion stage. This management makes waste into a pile that is endless and has no value. In the current era of Industrial Revolution 4.0, waste management can be customized so that waste becomes more useful and worth selling. This research was conducted in terms of building a digital startup that focuses on waste management. For the MVP (Minimum Viable Product) feature in this research, the Channel (media communication between users and digital startup) used in the form of Landing Page. The waste to be managed is grouped into organic waste and inorganic waste. Organic waste is managed using a composter media to produce fertilizers, and inorganic waste is managed so as to produce recycled goods that have a selling value. The focus of this research is digital based waste management in one of the big cities in Indonesia, Medan City. Research on Waste Management in the Era of Industrial Revolution 4.0 Based on Digital Startup is done so that people in Indonesia, especially in Medan City are aware of good waste management, so that one of the problems that often arise due to waste can be minimized. Digital startup in terms of waste management was established with the name of Angkut Sampah.Keywords: Waste Management, Industrial Revolution 4.0, Digital Startup, Angkut Sampah